Improvement of Muscle Quality of Grass Carp (Ctenopharyngodon idellus) With a Bio-Floating Bed in Culture Ponds - Zhang, Xi; Wang, Jingwei; Tang, Rong; He, Xugang; Li, Li; Takagi, Yasuaki; Li, Dapeng (Frontiers in Physiology, 2019)
Muscle quality and the physiological condition of fish are affected greatly by the culture environment. In aquaculture ponds, a bio-floating bed planted with vegetation is often used to improve water quality. This study investigated the growth and muscle quality of grass carp (Ctenopharyngodon idellus) cultured in ponds equipped with bio-floating beds. Fish were cultured in two replicated pond groups from May to November. Fish in the first group were cultured in the experimental ponds equipped with a bio-floating bed planted with Ipomoea aquatica, whereas fish in the other group were reared in the control ponds without a bio-floating bed. Compared with the control ponds, the experimental ponds had better water quality with significant lower concentrations of nitrite and ammonia. Grass carp in the experimental group obtained greater muscle weight gain, significant higher content of crude protein, and significant lower crude fat level than the fish in the control group. The muscular levels of pH, water-holding capacity, and antioxidant capacity decreased significantly in the control group compared to the experimental group. Texture profile analysis revealed higher values of hardness, springiness, gumminess, and chewiness of white muscle in the experimental group. The higher values of cohesiveness and resilience of white muscle occurred in the control group. The fillets of fish in the experimental group also received higher grades in the sensory evaluation of springiness, overall acceptability, aroma, and palatability. These results indicate that growth performance and muscle quality of grass carp were improved by the application of bio-floating bed technology in the culture ponds.